(untitled) - Barston, R. P. (London, 1980)
Throughout history man has used and been involved with the sea. It is only comparatively recently, however, within the last twenty years or so, that maritime issues - arising out of the use, exploration and exploitation maritime of the sea and its resources - have come to have much greater importance in international relations.
Keywords: Maritime law,Luật hàng hải